PENGETAHUAN SISWA SMP KELAS VIII DALAM MEMECAHKAN MASALAH MATEMATIKA NON GEOMETRI BERDASARKAN LEVEL 2 PERKEMBANGAN BERPIKIR VAN HIELE - Rosanti, Arminda Sari; Muh. Rizal, Muh. Rizal; Ismaimuza, Dasa (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The purpose of this study was to obtain a description of the knowledge of eighth grade students in solving mathematical problems of Â non geometry based on the level of development of the Van Hiele thinking. This study used qualitative methods with qualitative descriptive approach based on the troubleshooting steps proposed by Krulik and Rudnick. The results show that knowledge of the subjectis at level 2Van Hiele thinking developments in solving the mathematical problem of non geometry is as follows: (1) knowledge on the stage of reading and thinking about the problemis knowledge of the phrase